Robust graft survival and normalized dopaminergic innervation do not obligate recovery in a Parkinson disease patient. Issue 1 (6th January 2017) - Kordower, Jeffrey H.; Goetz, Christopher G.; Chu, Yaping; Halliday, Glenda M.; Nicholson, Daniel A.; Musial, Timothy F.; Marmion, David J.; Stoessl, A. Jon; Sossi, Vesna; Freeman, Thomas B.; Olanow, C. Warren
Abstract : Objective: The main goal of dopamine cell replacement therapy in Parkinson disease (PD) is to provide clinical benefit mediated by graft survival with nigrostriatal reinnervation. We report a dichotomy between graft structure and clinical function in a patient dying 16 years following fetal nigral grafting. Methods: A 55‐year‐old levodopa‐responsive woman with PD received bilateral putaminal fetal mesencephalic grafts as part of an NIH‐sponsored double‐blind sham‐controlled trial. The patient never experienced clinical benefit, and her course was complicated by the development of graft‐related dyskinesias. Fluorodopa positron emission tomography demonstrated significant increases postgrafting bilaterally. She experienced worsening of parkinsonism with severe dyskinesias, and underwent subthalamic nucleus deep brain stimulation 8 years after grafting. She died 16 years after transplantation. Results: Postmortem analyses confirmed the diagnosis of PD and demonstrated >300, 000 tyrosine hydroxylase (TH)‐positive grafted cells per side with normalized striatal TH‐immunoreactive fiber innervation and bidirectional synaptic connectivity. Twenty‐seven percent and 17% of grafted neurons were serine 129‐phosphorylated α‐synuclein positive in the left and right putamen, respectively. Interpretation: These findings represent the largest number of surviving dopamine neurons and the densest and most widespread graft‐mediated striatal dopamine reinnervation following a transplant procedure reported to date. Despite this, clinical recovery was not observed. Furthermore, the grafts were associated with a form of dyskinesias that resembled diphasic dyskinesia and persisted in the off‐medication state. We hypothesize that the grafted cells produced a low level of dopamine sufficient to cause a levodopa‐independent continuous form of diphasic dyskinesias, but insufficient to provide an antiparkinsonian benefit. ANN NEUROL 2017;81:46–57